Studi Kritis Terhadap Pembaharuan Pemikiran Pendidikan Islam Abdul Karim Amrullah, Abdullah Ahmad, Rahmah El-Yunisiyah, Dan Syekh Sulaiman Ar-Rasuli) - Muhammad Al fathoni; Zulmuqim; Fauza Masyudi (Journal of International Multidisciplinary Research, 2023)
This article discusses the renewal  of Islamic education thinking from several figures in promoting Islamic education in Minangkabau. Among these figures are Abdul Karim Amrullah, Abdullah Ahmad, Rahmah El-Yunusiyah, and Sheikh Sulayman Ar-Rasuli. Therefore, the author wants to study a critical study of Islamic education thoughts Abdul Karim Amrullah, Abdullah Ahmad, Rahmah El-Yunusiyah, and Sheikh Sulaiman Ar-Rasuli. Islamic education activities in Minangkabau were born and grew and developed along with the entry and development of Islam in Minangkabau. Indeed, Islamic education activities are important experience and knowledge for the continuity of the development of Islam and Muslims both in quantity and quality. The purpose of this article is to explain how the renewal of Islamic Education thought developed by the leaders of Education in Mingkabau. The method used in this research is a library study (library reasearch) whose data collection is carried out by studying literature theory that has been collected from various sources